Gendered Language in Different Cultural and Media Contexts - Zi, Chunmei (Transactions on Social Science, Education and Humanities Research, 2024)
This study attempts to explore how language expresses gender in different cultural and media contexts and how these expressions shape and reflect existing gender norms. Through in-depth analyses of the use of gendered language in American television advertisements, Japanese social media and South African textbooks, the paper seeks to demonstrate how language plays a key role in maintaining existing gender norms and challenging them. The study employs symbolic interactionism and critical social theory to analyse the collected data in detail with a view to better understanding the role of language in shaping gendered cognitive and behavioral patterns. In addition, the article explores the social effects of gender expressions in advertising, social media and educational materials, and based on the results of these analyses, a series of suggestions for promoting gender equality and diversity are proposed. By synthesizing cases from these different scenarios, the study aims to highlight the importance of understanding and changing gender expressions in order to promote a more egalitarian and inclusive social environment.